Participatory analysis of vulnerability to drought in three agro-pastoral communities in the West African Sahel - Ayantunde, Augustine A.; Turner, M.D.; Kalilou, A. (Springer, 2015)
Drought is one of the major climatic hazards impacting on the various sectors including crop and livestock in the West African Sahel. Pastoral and agro-pastoral communities in the region are regularly affected by drought, with vulnerability differing with gender, age, wealth status (access to cropland and livestock endowment), geographic location, social networks, and previous exposure to drought. Effective interventions require regular monitoring of vulnerability to drought, for which various quantitative and qualitative approaches exist. Qualitative assessments of vulnerability rely on participatory approaches with emphasis on involvement of the local communities in the analysis of their vulnerability to climate-induced stresses. In this study, we used a participatory approach to assess the vulnerability of three agro-pastoral communities in Niger to drought. The specific objective of this study was to assess the strength and limitation of a participatory vulnerability approach using a case study. According to the respondents in all the study sites, the incidence of drought has become more frequent in the last three decades compared to previous decades (before 1970). The impacts of drought on livelihoods according to the participants included food shortage, famine, forced sale of livestock to buy grain, decimation of livestock herds, and massive exploitation of woody plant species. The main weakness of participatory vulnerability assessments is the scalability of findings, as they are often location-specific. Therefore, participatory assessment should be complemented with more rigorous quantitative approaches to enhance applicability of the results to other locations with similar contexts.